Integration as a catalyst for assimilation - Oded Stark; Marcin Jakubek (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
We draw a distinction between the social integration and economic assimilation of migrants, and study an interaction between the two. We define social integration as blending into the host country's society, and economic assimilation as acquisition of human capital that is specific to the host country's labor market. We show that a non-integrated migrant finds it optimal to acquire a relatively limited quantity of human capital; with fellow migrants constituting his only comparison group, a non-integrated migrant does not have a relative deprivation-based incentive to close the income gap with the natives. However, when a migrant is made to integrate, his social proximity to the natives exposes him to relative deprivation, which in turn prompts him to form more destination-specific human capital in order to increase his earnings and narrow the income gap with the natives. In this way, social integration becomes a catalyst for economic assimilation.
urn:nbn:de:bsz:21-opus-69821
Keywords: D01; F22; J15; J24; J61; O15; Z10; 330; Assimilation; Social proximity; Interpersonal comparisons; Relative deprivation; Human capital formation